Embodying the spirit(s): Pentecostal demonology and deliverance discourse in Ethiopia - Haustein, Jörg (Ethnos, 2011)
The article explores Pentecostal embodiment practices and concepts with regard to Holy Spirit baptism and demon possession. The studied material is connected to a specific and highly controversial debate in Ethiopian Pentecostalism, which revolves around the possibility of demon possession in born-again and Spirit-filled Christians. This debate runs through much of Ethiopian Pentecostal history and ultimately is concerned with whether or how Christians can be seen to host conflicting spiritual forces, in light of the strong dualism between God and evil in Pentecostal cosmology. The article shows that the embodiment of spirits and/or the Holy Spirit is related to theological concepts of the self, because these concepts define what may or may not be discerned in certain bodily manifestations. Moreover, the article contends that this debate thrives on a certain ambiguity in spirit embodiment, which invites the discernment of spiritual experts and thereby becomes a resource of power.